THE EFFECT OF AUDITOR'S COMPETENCY, PROFESSIONALISM AND EXPERIENCE ON MATERIALITY LEVEL CONSIDERATIONS - Muhammad Naufal Hilmi; Novita Novita (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to prove the existence of a positive effect of competence, professionalism and experience of auditors on consideration of materiality levels. The sample of this research is 100 auditors obtained using purposive sampling technique. This research is a quantitative research with primary data through distributing questionnaires. Methods of data analysis in this study using the Partial Least Square (PLS) method. The results of this study prove that the competence, professionalism and experience of auditors have a positive effect on the consideration of the level of materiality of auditors who work in KAP DKI Jakarta Region.